Ce que (faire) parler veut dire. Enjeux méthodologiques et épistémologiques des récits de maladie en psychiatrie - Nicolas Henckes; Nicolas Marquis (Anthropologie & Santé)
While conducting interviews with sick people has practically become mandatory for any piece of social science research dealing with mental health issues, there are few if any methodological developments in the literature about the status of this discourse. Yet most field researchers are confronted with the fact that mental illness, because it alters the ability of people to enter into proper relationships, undermines the framework of the social science interview. By comparing a series of textbooks on social science methodology on the one hand, and writings by clinicians seeking to characterize psychosis as a form of life on the other hand, this article tries to identify more precisely these difficulties and possible ways to overcome them. More broadly, we ask whether it would be possible to set up a framework within which social scientists would be able to use clinical knowledge on mental illness without adopting a denunciative or, on the contrary, a submissive stance towards this knowledge.